Acceleration of Regeneration of the Corneal Endothelial Layer After Descemet Stripping Induced by the Engineered FGF TTHX1114 in Human Corneas in Organ Culture. Issue 2 (28th February 2023) - Pizzuto, Sarah; Duffey, Grace; Weant, Jessica; Eveleth, David
Abstract : Purpose: Descemet stripping only (DSO, descemetorhexis without endothelial keratoplasty) is increasing in clinical use but can impose long recovery times. The objective of this research was to determine whether TTHX1114, an engineered analog of FGF1, could accelerate healing in corneas after DSO. Methods: Corneas obtained from eye banks were placed into suspension culture and subjected to DSO with a procedure comparable with that used clinically. The healing of the stripped area and the regeneration of the corneal endothelial cell (CEC) layer were evaluated intermittently for 14 days using trypan blue staining, alizarin red staining, and immunohistochemistry. Results: Corneas subjected to DSO showed about 30% of the stripped area healed after 14 days in culture while those treated with TTHX1114 healed 81%. The healed area was similar in both normal corneas and corneas judged by the eye banks to be dystrophic. The regeneration of the endothelial layer in the stripped area was substantially more complete in TTHX1114-treated corneas, most of which demonstrated a contiguous monolayer of CECs expressing ZO-1 at the cell–cell junctions. In corneas not subject to DSO, incorporation of EdU, a marker of proliferation, was stimulated by TTHX1114 treatment. Conclusions: The corneal organ culture model recapitulated clinical observations of DSO, only with much more rapid recovery. Within the immediate postsurgical time frame of 2 weeks, treatment with TTHX1114 stimulated near-total regeneration of the CEC layer, suggesting that TTHX1114 may be useful as an adjunct to DSO.